Desafios da motivação no trabalho: um estudo no setor público - SILVA, Andresa Nunes da; FALEIROS, Fernandes Izabel Cristina (109, 2024)
Um setor público com servidores satisfeitos em seu ambiente de trabalho, garante uma melhor qualidade na administração, refletindo diretamente na população do município. Entretanto, ao mesmo tempo em que se observa um volume considerável de profissionais se dedicando aos estudos, visando obter um cargo público, é frequente ouvir as pessoas reclamando dos serviços públicos de forma geral. Assim, o presente estudo visa entender os fatores que influenciam na motivação ou desmotivação dos servidores públicos em seu ambiente de trabalho, buscando entender o que leva a pessoa a lutar e se dedicar tanto para conquistar o ingresso no serviço público e posteriormente se apresentar desmotivado e desengajado, bem como entender qual é o papel da área de Gestão de Pessoas diante desse cenário. Dessa forma, será possível contribuir para a adequação das políticas e práticas institucionais, beneficiando os servidores e os munícipes. Para tanto, será realizada a pesquisa qualitativa de caráter descritivo, por meio de pesquisa bibliográfica em materiais científicos sobre o assunto e pesquisa e campo na Prefeitura de uma cidade do Interior de São Paulo. Os resultados indicam que as pessoas se percebem motivadas, porém relataram estar insatisfeitas com a limitada possibilidade de crescimento na instituição pública, bem como com a forma de gestão.

A public sector with employees who are satisfied in their work environment guarantees better quality in administration, directly reflecting on the population of the municipality. However, at the same time as there is a considerable number of professionals dedicating themselves to studies, aiming to obtain a public position, it is common to hear people complaining about public services in general. Thus, the present study aims to understand the factors that influence the motivation or demotivation of public servants in their work environment, seeking to understand what leads people to fight and dedicate themselves so much to gain entry into the public service and subsequently appear unmotivated and disengaged, as well as understanding the role of the People Management area in this scenario. In this way, it will be possible to contribute to the adequacy of institutional policies and practices, benefiting employees and citizens. To this end, qualitative research of a descriptive nature will be carried out, through bibliographical research on scientific materials on the subject and field research in the City Hall of a city in the interior of São Paulo. The results indicate that there is a great variation in the motivation or lack of motivation of employees. The data researched and samples collected show that although employees value their stability, benefits acquired and work performed, they yearn for other forms of recognition and personal growth in addition to professional development. It is noticeable that the level of motivation that leads them to a commitment to quality is directly linked to the employee as a person. Thus, we can say that personal and professional aspects go hand in hand, as you will be able to recognize throughout this article.
Challenges of motivation at work: a study in the public sector
Keywords: Liderança; Motivação; Motivação do empregado; Gestão e Negócios